A17 THE NEUROPEPTIDE VIP REGULATES INTESTINAL IMMUNITY THROUGH MODULATING THE ACTIVATION AND RECRUITMENT OF GROUP 3 INNATE LYMPHOID CELLS. (15th March 2019) - Yu, H; Yang, H; Ma, C; Liang, Q; Bosman, E S; Graef, F A; Reid, G S; Waschek, J A; Osborne, L; Vallance, B; Jacobson, K
Abstract: Background: Group 3 innate lymphoid cells (ILC3s) are a class of innate lymphocytes that are emerging as key players in regulating intestinal inflammation, immunity and homeostasis. Through the production of the cytokine IL-22, ILC3s can modulate the function of intestinal epithelial cells (IECs), helping to maintain the IEC barrier integrity and promoting host defense against bacterial pathogens (such as Citrobacter rodentium ). Recently, a handful studies have shown that ILC3s can communicate with the nervous system in the gut where neurons and immune cells are enriched. It remains largely unexplored how this neuroimmune communication regulates the number and function of ILC3s in the gut. Aims: To understand how the neuropeptide - vasoactive intestinal peptide (VIP), controls the expansion and function of ILC3s thereby regulating intestinal immunity under baseline and infection conditions. Methods: Wildtype (WT), Vip -/- and Rag1 -/- mice were used. ILC3s and dendritic cells were isolated from the intestinal lamina propria using percoll gradients. ILC3s migration towards VIP was measured by a chemotaxis assay. The number and function of ILC3s was assessed using FACS. IL-22, RegIII-β, and RegIII-γ production was quantified by qPCR and/or ELISA. WT and Vip -/- mice were infected with C. rodentium for 4–10 days, and their susceptibility to infection assessed by measuring body weight loss, bacterial counts, and histological changes. Recombinant VIP, IL-22 or retinoic acid (RA) was IP injected into Vip -/- mice, with the mice subsequently analyzed for their susceptibility to C. rodentium infection. ILC3s were also isolated from Rag1 -/- mice and injected into Vip -/- mice by the IV route, followed by infection with C. rodentium . Results: VIP induced ILC3s migration through the receptor VPAC2. VIP also promoted gut homing receptor CCR9 expression on intestinal ILC3s, by enhancing RA production by intestinal dendritic cells. The loss of VIP led to reduced activation and recruitment of intestinal ILC3 cells, less IL-22 production, and abnormal IEC barrier function. Accordingly, Vip -/- mice proved highly susceptible to C. rodentium infection, suffering dramatic body weight loss, increased pathogen colonization, and worsened intestinal damage. Notably, recombinant IL-22 adminstration was sufficient to rescue Vip -/ - mice from C. rodentium infection. Moreover, treatment with RA or VIP, or adoptive transfer of ILC3 cells were all able to increase the intestinal production of IL-22 and protect Vip -/ - mice from infection. Conclusions: Our results reveal a novel neuroimmune axis whereby the neuropeptide VIP controls the activation and recruitment of ILC3s in the gut, thereby playing a key role in promoting mucosal defense against intestinal pathogens. Funding Agencies: CCC, CIHRNSERC